Principles of State Regulation of Business in the Republic of Uzbekistan - Abdumalikovich, Bektemirov Abdukhamid; Erkinboy oʻg‘li, Salaev Islombek; Karim qizi, Umurzoqova Sevinch (Journal of Innovation in Education and Social Research, 2024)
We must remove all obstacles and pitfalls to the development of entrepreneurship, which is the main force driving our economy. For this purpose, in our Constitution, we must strengthen the norm that the state creates all conditions for the free movement of goods, services, labor and financial resources in our country, for the development of internal and external trade. This is the demand of the times and the reforms we have started.